Investigating the impact of fungicides and mungbean genotypes on the management of pod rot disease caused by Fusarium equiseti and Fusarium chlamydosporum - Buttar, Harwinder Singh; Singh, Amarjit; Sirari, Asmita; Anupam,; Kaur, Komalpreet; Kumar, Abhishek; Lal, Milan Kumar; Tiwari, Rahul Kumar; Kumar, Ravinder (Frontiers in Plant Science, 2023)
Mungbean is a vital pulse crop in India that can thrive in dry-land conditions and is grown in three seasons, with the added benefit of being used as green manure due to its ability to fix atmospheric nitrogen. Recently, pod rot disease has emerged as a serious threat to mungbean cultivation in India. In this study, morpho-molecular identification of associated pathogens, bio-efficacy of systemic and non-systemic fungicides and genotype screening was performed during the years 2019 and 2020. The pathogens associated with this disease were confirmed on the basis of morphological and molecular characterization. For the molecular characterization, the translation elongation factor 1-alpha (tef-1) gene sequences were amplified by using primers (EF1& EF2). Under in vitro, conditions Trifloxystrobin+ Tebuconazole 75% WG was found to be the most effective against Fusarium equiseti (ED50 2.39 µg ml-1) and Fusarium chlamydosporum (ED50 4.23 µg ml-1) causal agents of pod rot of mungbean. Under field conditions, three applications of Trifloxystrobin+ Tebuconazole 75% WG @ 0.07% as a foliar application at fortnightly intervals starting from the last week of July proved to be the most effective against pod rot disease on mungbean cultivars i.e., ML 2056 and SML 668. To identify the potential resistance sources, seventy-five interspecific derivative and mutant lines of mungbean were screened for disease reaction to pod rot under natural epiphytotic conditions for the years 2019 and 2020. Genotypic differences were observed for resistance to pod rot disease. The study revealed that among the tested genotypes, ML 2524 exhibited resistance to pod rot disease, with a disease incidence of 15.62% and disease severity of 7.69%. In addition, forty-one other genotypes were found to be moderately resistant (MR) to the disease. Altogether, the identified management options will offer an immediate solution to manage this disease under recent outbreak conditions and pave a path for futuristic disease management using identified resistant sources in breeding program.